80-(4x+7)=4(x+7)+x

Simple and best practice solution for 80-(4x+7)=4(x+7)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 80-(4x+7)=4(x+7)+x equation:


Simplifying
80 + -1(4x + 7) = 4(x + 7) + x

Reorder the terms:
80 + -1(7 + 4x) = 4(x + 7) + x
80 + (7 * -1 + 4x * -1) = 4(x + 7) + x
80 + (-7 + -4x) = 4(x + 7) + x

Combine like terms: 80 + -7 = 73
73 + -4x = 4(x + 7) + x

Reorder the terms:
73 + -4x = 4(7 + x) + x
73 + -4x = (7 * 4 + x * 4) + x
73 + -4x = (28 + 4x) + x

Combine like terms: 4x + x = 5x
73 + -4x = 28 + 5x

Solving
73 + -4x = 28 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
73 + -4x + -5x = 28 + 5x + -5x

Combine like terms: -4x + -5x = -9x
73 + -9x = 28 + 5x + -5x

Combine like terms: 5x + -5x = 0
73 + -9x = 28 + 0
73 + -9x = 28

Add '-73' to each side of the equation.
73 + -73 + -9x = 28 + -73

Combine like terms: 73 + -73 = 0
0 + -9x = 28 + -73
-9x = 28 + -73

Combine like terms: 28 + -73 = -45
-9x = -45

Divide each side by '-9'.
x = 5

Simplifying
x = 5

See similar equations:

| 2(2x-1)=3(x+1) | | x+73x=77 | | 6b^2+19b-36=0 | | 6(d+6)=4(d-6)-d | | -24(x-2)= | | 2(n+4)=8-6(n-4) | | -24(x+2)= | | -12(2x-12)= | | 2x-2y=-1 | | m+m(0.07)= | | 2x-3y+x+5y-3= | | y=5x-13 | | (57x+58y)+(-5x+41y)= | | (18x+2y)+(36x+27y)= | | (63x+50y)-(17x+35y)= | | (64x+48y)-(9x-16y)= | | 5x-3=-10x+8 | | 2x+8=-28 | | (30+5x)+(15+10x)=180 | | 6x+5=9x-19 | | 64-7x=2x+17 | | 2x+3x+1=12-6 | | 6x+14=-40 | | 8-9[9-(3y-7)]= | | 6-9x=29-16x | | 61-7x=11x+23 | | 13-8x=39-22x | | 6-9x=29-6x | | x/2+1=5 | | 2(x-3)=-3x+4 | | 75.60=9x | | 21-2(3+5)= |

Equations solver categories